Practical Issues to Prevent Stroke Associated with Non-valvular Atrial Fibrillation - Kim, Chi Kyung (Korean Stroke Society, 2013)
Stroke associated with non-valvular atrial fibrillation (NVAF) is one of the most important subtypes of ischemic stroke, and its importance is becoming even more apparent in an aging population. To assess the risk of stroke associated with NVAF, the CHADS(2) and CHA(2)DS(2)-VASc scores are mainly used. Such scores can be used to predict the recurrence and prognosis of ischemic stroke. In addition, new oral anticoagulants (NOACs) and devices are being evaluated in the prevention of stroke associated with NVAF in addition to treatment with the conventional oral anticoagulant, warfarin. Since clinical experience with NOACs is not globally sufficient, a cautious approach is needed.